Studi Kepiting Mangrove di Delta Mahakam, Kalimantan Timur - Pratiwi, Rianta (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2007)
The research was carried out in July 2004 at Makaham Delta, East Kalimantan. Thisresearch observed the diversity and the distribution pattern of mangrove crabs atmuara Ilu, Kaely, Bayor, and Beji. There are 33 species consisting of 7 families and 6908individu of crabs found in this research. Most of the mangroves crabs are clumpdistributed. The research method by using frame transects 1 m2 x 1 m2 with 5 up to 10meters distance (based on the thickness of mangrove in those areas). The distributionpattern of crabs analyze by using Index Morisita according to Brower and Zar.